2014
DOI: 10.5812/jamm.22517
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Sprains at a Military Male School: Taping Versus Bracing

Abstract: Background: Surgical treatment of lumbar intervertebral disc herniation is a critical procedure due to the proximity of the operation field to neural structures. Providing a bloodless field and optimizing surgeon vision is of high value in this regard. Total intravenous anesthesia with propofol and inhalation anesthesia with isoflurane are both used in spine surgeries. Both of these agents have vasodilator properties that could be benefited in inducing controlled hypotension as a blood sparing technique. We so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…() and Najafipour et al . (), who found that taping was cheaper than ankle brace. The increased cost of ankle brace may be due to the initial material cost (Lardenoye et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Najafipour et al . (), who found that taping was cheaper than ankle brace. The increased cost of ankle brace may be due to the initial material cost (Lardenoye et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Najafipour et al . ). To avoid these complications in patients undergoing the intervention, at least one visit to physiotherapist per week is required (Lardenoye et al .…”
Section: Introductionmentioning
confidence: 97%
“…11,43,45 For example, a cost-effectiveness study 11 that compared return-to-work postacute ankle sprains after either semi-rigid ankle bracing or taping, extracted benefit data from a study of tubular bandage 10 despite no evidence to suggest that the HR-QoL benefits of taping are comparable with tubular bandage. Given the prevalence of tapingrelated skin complications 50,[63][64][65] that reduce HR-QoL, it is likely that the benefit of the taping intervention and the subsequent costeffectiveness outcome have been overstated.…”
Section: Model Input Datamentioning
confidence: 99%